2019
DOI: 10.3892/ol.2019.11204
|View full text |Cite
|
Sign up to set email alerts
|

mi‑R4435‑2HG promotes proliferation and inhibits apoptosis of cancer cells in ovarian carcinoma by upregulating ROCK2

Abstract: The present study aimed to investigate the involvement of long noncoding RNA mi-R4435-2HG in ovarian carcinoma. mi-R4435-2HG and Rho-associated protein kinase 2 (ROCK2) were demonstrated to both be upregulated in ovarian carcinoma. mi-R4435-2HG and ROCK2 were positively correlated in both tumor and healthy tissues. mi-R4435-2HG overexpression mediated the upregulation of ROCK2, while upregulation of ROCK2 did not affect mi-R4435-2HG. Overexpression of mi-R4435-2HG and ROCK2 led to promoted proliferation and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…The present study identified ROCK2 as a novel target gene of miR-181a-5p in CRC cells. ROCK2 has been reported to play a vital role in multiple cellular processes, such as proliferation ( 37 ), apoptosis ( 38 ), DNA repair ( 39 ) and invasion ( 40 ). A study indicated that ROCK2 contributed to the invasion and metastasis of CRC ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study identified ROCK2 as a novel target gene of miR-181a-5p in CRC cells. ROCK2 has been reported to play a vital role in multiple cellular processes, such as proliferation ( 37 ), apoptosis ( 38 ), DNA repair ( 39 ) and invasion ( 40 ). A study indicated that ROCK2 contributed to the invasion and metastasis of CRC ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…ROCK2 and CTSB gains or amplifications were shared among six samples (both STUMPs and LMSs). ROCK2 (Rho associated coiled-coil containing protein kinase 2) upregulation has been described in human glioblastoma CSCs [13], in gastric cancer [14], as well as in ovarian cancer samples [15]. Moreover, ROCK2 expression level has been associated with worse prognosis in osteosarcoma tissues [16].…”
Section: Discussionmentioning
confidence: 99%
“…miR-4435-2HG, an oncogenic lncRNA, was shown to promote the expression of ROCK2, and inhibited the apoptotic death of ovarian cancer cells (57). miR4435-2HG overexpression induced the upregulation of ROCK2 in ovarian cancer UWB1.289 cells (57). Similarly, other lncRNAs that promote carcinogenesis have also been identified in ovarian cancer.…”
Section: Regulation Of Rock2 By Lncrnas: Oncogenic Rolementioning
confidence: 98%